Annual Plan 1994-95 Himachal Pradesh - Planning Commission (Planning Commission, 1994)
The population of Himachal Pradesh according to 1991 Census is 51.70 lakh out of which 47.21 lakh (91.31) percent lives in rural areas and 4.49 lakh (8.69) percent in Urban areas, thus the majority of population is associated with such economic activities as are related to rural economy The main workers and marginal workers constitutes 22.14 lakh which forms 42.82 percent of the total population. The following table gives the distribution of main workers, marginal workers and non-workers as classified in 1991 Census.
Himachal Pradesh